Clinical validation of an automated reverse transcription-insulated isothermal PCR assay for the detection of severe acute respiratory syndrome coronavirus 2 - Pai-Ling Chang; Chia-Yi Lin; Cheng-Pin Chen; Yi-Chun Lin; Hui-Chun Hu; Shu-Hsing Cheng; Chien-Yu Cheng (Journal of Microbiology, Immunology and Infection, 2021)
To determine clinical performance of the single-target SARS-CoV-2 orf 1 ab reverse transcription-insulated isothermal PCR (RT-iiPCR) assay, the positive percentage agreement between this assay and a laboratory real-time RT-PCR assay was 96.8% (30 of 31; 95% confidence interval [CI], 90.5%–100%) and the negative percentage agreement was 97.1% (67 of 69; 95% CI, 93.1%–100%).